Pneumoperitoneum in laparoscopy and preoperative antihypertensive agents: A retrospective study - Kim, Hyunjee (Exp Ther Med, 2019)
The purpose of the current study was to investigate the effects of preoperative antihypertensive agents on blood pressure (BP) changes after intraperitoneal CO(2) insufflation during laparoscopic surgery. The medical records of patients (≥50 years old) undergoing laparoscopic colon surgery were retrospectively analyzed (n=342). The patients were divided into four groups: normotensive group (group N), monotherapy with angiotensin receptor blockers (ARBs) (group A), monotherapy with calcium channel blockers (CCBs) (group C), and combination therapy with ARBs and CCBs (group AC). The systolic BP changes were investigated, and their correlations with preoperative pulse pressure were analyzed. The degree of increase from baseline BP to that after CO(2) insufflation was significantly lower in groups A [difference vs. group N, 17.8; 95% confidence interval (CI), 7.8–27.8; P=0.001) and AC (18.2; 95% CI, 8.7–27.7; P<0.001] compared with groups N and C. The incidence of intraoperative hypotension was not significantly different among the groups. In groups A and AC, the preoperative pulse pressure showed a strong correlation (r=0.73 and 0.83, respectively) with the increase in BP after CO(2) insufflation. In conclusion, patients with hypertension who received ARBs before surgery showed a strong correlation between the preoperative pulse pressure and BP fluctuation immediately after CO(2) insufflation. Small BP fluctuations are suggested to indicate the positive role of ARBs. Large randomized controlled trials are required to validate these results and assess the effect of each antihypertensive agent. This trial was registered (Trial registration: http://www.who.int/ictrp/network/cris2/en/; CRIS; KCT0002595) on the 23 November 2017.